2021
DOI: 10.1111/1468-5973.12371
|View full text |Cite
|
Sign up to set email alerts
|

Crisis management as practice in small‐ and medium‐sized enterprises during the first period of COVID‐19

Abstract: This article draws attention to the social context and working methods in crisis management. Based on 1000 interviews with business leaders in Swedish small‐ and medium‐sized enterprises (SMEs), we analyze crisis management in practice and ask: What social contexts do business leaders use in crisis management, and what working methods do they rely on? Most companies in this study do not have any form of crisis group; rather, they deal with issues reactively as they occur. Few of the companies work continuously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 58 publications
(131 reference statements)
0
22
0
2
Order By: Relevance
“…While crisis and threats to business can be commonplace, COVID-19 has brought a much higher level of crisis with a global impact and how long this could go on. Fasth, Elliot, and Styhre (2021) conducted a study of 1,000 SME business leaders in Sweden to understand their crisis management plans. These research findings indicated that many SMEs rarely had a crisis plan and were subject to large revenue losses.…”
Section: Covid-19 Pandemic and Research Findings Discussionmentioning
confidence: 99%
“…While crisis and threats to business can be commonplace, COVID-19 has brought a much higher level of crisis with a global impact and how long this could go on. Fasth, Elliot, and Styhre (2021) conducted a study of 1,000 SME business leaders in Sweden to understand their crisis management plans. These research findings indicated that many SMEs rarely had a crisis plan and were subject to large revenue losses.…”
Section: Covid-19 Pandemic and Research Findings Discussionmentioning
confidence: 99%
“…Second, no central directory exists for all deployed COVID-19 CMTs and their characteristics (cf. Klinger et al, 2022), and CMTs were rarely set up in small and medium-sized enterprises (Fasth et al, 2022). Thus, it is difficult to estimate how representative our sample was for the whole population.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…In response to the massive strain of COVID-19 for societies, initial descriptive analyses and qualitative interviews had been conducted with crisis management teams (CMTs; e.g., Fasth et al;Klinger et al, 2022;Thielsch et al, 2021), revealing quite specific demands, such as continuously high workload or personal affectedness (e.g., because friends and family might become infected), but also certain resources that were helpful for CMT members. However, such analyses mainly focus on the first months after the pandemic had started.…”
Section: Introductionmentioning
confidence: 99%
“…Learning to know each other this way appears to be an important mechanism, perhaps even more important than implementing fixed plans. Fasth et al (2021) It is a saying that the Norwegian county governor institution is a bold construction. It is thrilling to look into the history, with all its tensions and challenges, noting how this institution can balance different actors to establish a common understanding of a pandemic.…”
Section: Seeing the Totalitymentioning
confidence: 99%